Implementation of Guidance And Counseling Services By Primary School Teachers - Yusra, Wahyuni Eva; Silvianetri, Silvianetri (Universitas Islam negeri Mahmud Yunus Batusangkar, 2022)
This research aims to find out how the class teachers implement the guidance and counseling services in primary schools. This research used descriptive qualitative method. Data were collected through observation, interview, and documentation. The informants were class teachers, school principals, and deputy of principal for curriculum affair. The data were analyzed by doing data reduction, data display and making conclusion or verification. Source triangulation was chosen for data trustworthiness. The results described that the guidance and counseling services were implemented quite well by teachers and guided learning even created. The implementation of guidance and counseling services by teachers in primary schools was customized with the core and basic competence written in the lesson plan every semester. Teachers could know their students better by focusing on guidance activities to improve the effective and efficient teaching and learning process.┬á